(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Identification of sex is an important issue in forensic dentistry and in medico-legal investigations. The skeletal components most often investigated for sex determination are the pelvis and skull with mandible. In human remains, next to pelvis, mandible is used to estimate age, sex, and race. Mandibular ramus and gonial angle can be used to determine sex. Study aimed to measure, compare, and evaluate various measurements of ramus, gonial angle and bigonial width as observed on panoramic radiographs. Material and methods: Panoramic radiographs of 25 males and 25 females (age 11-19years) were taken randomly, measurements were made using two methods. In 1st method (ramus), measurements of height and breadth of ramus were taken and in 2nd method (gonial), measurements of gonial angle and bigonial width were made. The measurements were subjected to discriminant functional analysis. Results: In ramus method, condylar, coronoid and projection height of ramus was higher in males (p